Is crowding out of private sector credit inhibiting Africa's growth? - Ahmed Attout; Alfredo Baldini; Vivian F. de O. Schmidt; Sanne Zwart (European Investment Bank (EIB), 2022)
During the pandemic, African banks rebalanced their portfolio towards sovereign assets, and crowding out of credit to private sector intensified. Policy support, however, averted a credit crunch. The increase in public debt across Africa due to the COVID-19 crisis intensified crowding out of credit to the private sector. As the economic recovery got underway, credit demand by the private sector picked up again in 2021, thus competing with government securities for funding. The analysis presented in this study confirms that crowding out has become more severe, but that timely policy support averted a credit crunch. Evidence of an increased sovereign-bank nexus highlights risks to macro-financial stability, especially as sovereign creditworthiness is deteriorating. Reducing excessive sovereign borrowing and strengthening countries' public debt management and transparency will help to contain crowding-out effects. Domestic and international development finance institutions can support these efforts by catalysing private sector resources and providing technical assistance.
Keywords: 330; Africa; bank; banking; coronavirus disease; economic development; economic situation; macroeconomics; public debt; Anleihe; Öffentliche Schulden; Private Investition; Kreditgeschäft; Privatwirtschaft; Wirtschaftswachstum; Verdrängungseffekt; Afrika